Genetic Variability and Performance of MPOB-Nigeria Dura x AVROS Pisifera Planting Materials - Abu Bakar, Nor Azwani; Ahmad Malike, Fadila; Amiruddin, Mohddin; Abdullah, meilina ong (International Journal of Oil Palm, 2022)
A long-term evaluation on fourteen D x P progenies of introgressed MPOB-Nigeria dura x AVROS pisifera were laid down in a randomized complete block design in two replicates with 371 palms in 2002. The aim was to evaluate the performance of fresh fruit bunch yield, bunch quality and vegetative traits among progenies. Analysis of variance revealed highly significant difference for all traits, indicating the existence of substantial variability within these population. In all cases, the phenotypic coefficient of variance was higher than the genotypic coefficients. Broad-sense heritability values estimated ranged from 8.85% to 100% for all the traits studied. The fresh fruit bunch also was found to be positively and highly correlated with bunch number, average bunch weight, oil yield ratio and kernel yield ratio. PK 3248 and PK 3166 were preferred as potential parental lines in breeding programmes and to be included in introgression with advanced breeding populations such as Deli dura.